The role of Th17 and regulatory T cells (TREGs) in immunomodulation of experimental periapical lesions - Francisconi, Carolina Fávaro (2016)
The pathogenesis of periapical lesions is determined by the balance between host proinflammatory immune response and counteracting anti-inflammatory and reparative responses. In this context, different subtypes of lymphocytes and their products have been implicated in periapical lesion pathogenesis, such as regulatory T cells (Tregs) and Th17. While Tregs has been demonstrated as potential immunoregulatory agents, Th17 has been correlated with greater severity of disease. In this study, we investigated (in a cause-and-effect manner) the involvement of Tregs and Th17, besides the impact of different therapies in the progression of experimental periapical lesions. With this aim, periapical lesions were induced (pulp exposure and bacterial inoculation) in C57Bl/6 (wild-type), IL-17KO and CCR4KO mice and treated with antiglucocorticoid-induced TNF receptor family regulated gene (anti-GITR) to inhibit Treg function or alternatively with CCL22-releasing, poly lactic-glycolic acid particles to induce site-specific migration of Tregs. Furthermore, WT mice were treated with anti-RANKL using continuous or intermittent protocols, and with anti-TNF therapy as a control. After treatment, lesions were analyzed for Treg or Th17 influx and phenotype, overall periapical bone loss, and inflammatory/immunologic and wound healing marker expression (RealTimePCRarray, ELISA). Treg inhibition by anti-GITR or CCR4 depletion results in a significant increase in periapical lesion severity, associated with upregulation of proinflammatory, Th1, Th17, and tissue destruction markers in parallel with decreased Treg and healing marker expression. The local release of CCL22 in the root canal system resulted in the promotion of Treg migration in a CCR4-dependent manner, leading to the arrest of periapical lesion progression, associated with down regulation of proinflammatory and tissue destruction markers in parallel with increased Treg and healing marker expression. Anti-RANKL treatment arrested lesion development, but prompted a continuous inflammatory response characterized by unremitting elevated expression of proinflammatory cytokines and tissue destructive mediators, and decreased expression of Tregs and wound healing markers levels. This treatment triggered lesion development relapse and was associated with high TCD4 effector/suppressor cells ratio and active lesions gene expression signature. Anti-TNF treatment limits lesions progression and does not drives lesions relapse upon cessation, being associated with attenuated host response. Finally, the absence of IL-17 results in a significant decrease in periapical lesions severity, associated with upregulation of healing markers and antiinflammatory cytokines, in parallel with decreased expression of tissue destruction markers and proinflammatory cytokines. Indeed, histomorphometric analysis showed lower concentration of osteoclasts, neutrophils and mononuclear cells in periapical lesions without IL-17. Therefore, we concluded that regulatory T cells are essential in the control of apical periodontitis, while Th17 cells accentuate the lesions severity. Compared with other clinical strategies, such as anti-RANKL therapy, which perpetuates the host inflammatory response prompting lesion relapse, chemoattraction of Treg as well as inhibition of Th17 may be promising strategies for the clinical management of periapical lesions.